Transparansi dalam Tata Kelola Perusahaan Air Minum Daerah di Kabupaten Minahasa - Siwij, Devie S. R.; Dilapanga, Abdul R.; Polii, E. H. (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to evaluate the implementation of the principle of Transparency in the Regional Drinking Water Company (PDAM) of Minahasa Regency whether it is in accordance with Government Regulation Number 54 of 2017 article 92 concerning Good Corporate Governance based on the GCG policy instrument by the National Committee on Governance Policy in 2006. The research method uses a type of descriptive qualitative research, and data collection techniques: interviews, observation, and documentation. In-depth interviews were conducted with logical questions based on guidelines, interviews were conducted with strong intimacy, and researchers appreciated the value of interviews as a data collection tool. Data analysis techniques: qualitative data analysis with data reduction, presentation, and data verification. The results of the research show that transparency is not optimal. Recommendations for Regional Heads as Capital Owners (KPM) and PDAM Management Transparency need to be optimized by maximizing the right technology and policies.